Caseous necrosis of the mitral annulus: a new feature of drug-induced valvular heart disease? Case series. Issue 1 (16th December 2021) - Leblon, Tiphaine; Riolet, Clemence; Ennezat, PierreVladimir; Marechaux, Sylvestre
Abstract: Background: Drug-induced valvular heart disease (DI-VHD) is a well-defined condition associated with specific pathology features. However, clinical presentations may broadly vary and thereby make DI-VHD diagnosis more challenging. Case summary: We report two patients with a history of benfluorex administration, who developed extensive mitral calcific lesions which evolved towards caseous necrosis. Discussion: Prospective follow-up over several years of these two patients who initially had typical DI-VHD findings provided monitoring evidence of extensive calcifications and subsequent caseous necrosis. These reports suggest a link between calcific heart injury and benfluorex exposure. The diagnosis of DI-VHD may be overlooked at this late stage.